Development of anthocyanin markers: gene mapping, genomic analysis and genetic diversity studies in Ipomoea species - Arizio, Carla Marcela; Costa Tártara, Sabrina María; Zunino, Ignacio; Manifesto, Maria Marcela (Academia Brasileira de Ciencias, 2022)
The anthocyanins are pigments responsible for a wide range of colours in plants, from blue, red and purple, play essential biological roles as well as their genes are evolutionarily conserved. Purple sweet potatoes have anthocyanins as the predominant colour, even though they are present in orange roots masked by carotenoids. Several studies have focused on molecular aspects of anthocyanin genes, mainly in wild Ipomoea species, although the structure and segregation analysis of those genes in sweet potato hexaploid species are still unknown. Based on an “exon-primed intron crossing” (EPIC) approach, fourteen pairs of primers were designed, on fi ve structural anthocyanin genes as candidates. The strategy exploits the Intron Length Polymorphism (ILP) from Candidate Genes (CG), resulting in 93% of successful markers giving scorable and reproducible alleles. The results allowed to defi ne partial structure and sequence of the introns and exons from the selected CG, and to determine patterns of sequence variation. The evaluation of marker dosage and allelic segregations in an Ipomoea batatas (L.) Lam mapping population identifi ed several alleles for linkage analysis. The study validated the utility of ILP-CG markers for genetic diversity and conservation applicability and a successful amplifi cation gradient across wild Ipomoea species validated their transferability